The impact of the Gannon Storm of May 2024 on the radiation fields at aviation altitudes and in low earth orbits - Schennetten, Kai; Matthiä, Daniel; Meier, Matthias M.; Berger, Thomas; Wirtz, Michael (Frontiers in Astronomy and Space Sciences, 2024)
In May 2024 the strongest geomagnetic storm since the Halloween storms of 2003 occurred. Media reported worldwide about the space weather situation and its effects on the infrastructure. Of particular interest were reports claiming severe effects on the radiation exposure at aviation altitudes, although no data supporting this assertion were available at that time. In this work the different aspects that affect the radiation exposure at aviation altitudes are discussed for the event. Furthermore, the corresponding dose rates are evaluated and compared to data from Low Earth Orbit. Model calculations indicate an additional contribution to the radiation field at aviation altitudes due to this extraordinary space weather situation, although the dose rates were still in the lowest category D0 of the space weather D-index, i.e., within the dose rate variation of a solar cycle.